4g-g-5=3

Simple and best practice solution for 4g-g-5=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4g-g-5=3 equation:


4g-g-5=3

We simplify the equation to the form, which is simple to understand
4g-g-5=3

We move all terms containing g to the left and all other terms to the right.
+4g-1g=+3+5

We simplify left and right side of the equation.
+3g=+8

We divide both sides of the equation by 3 to get g.
g=2.66666666667

See similar equations:

| 6(x-8)=5x-6 | | 3/4x4/5 | | 0.50y+10x=1044 | | 0.75x+3.50=7.00 | | 8(w-3)=7w-2 | | 6x-7+x=7x+4-2x | | 6x-3y=30 | | 18x+10-14x=-34 | | 9x-7=28+4x | | m/4-4.6=-3.1 | | 18=r(2) | | X=5.6 | | 7(1)-8y=56 | | 5=4(3y-2) | | 11x-18=3+8x | | 6x+8x+10=66 | | 6-(3z-1)=6-4z | | 7x-8(0)=56 | | 6x+10=4x-8 | | r^2-15=-2r | | 9(y-6)=8(y-9) | | -1/2x^2+100x | | 7(0)-8y=56 | | 13x-12=49x+24 | | 24z-48z=.72 | | 5x-14=x-(24+4x) | | w-3/2=5/8 | | -11/2h=4 | | 4(x-4)+6=6x-2(3+x) | | x+(x-12)=58 | | -31/3b=5 | | 14x-8x+9=33 |

Equations solver categories